2011
DOI: 10.1364/ol.37.000112
|View full text |Cite
|
Sign up to set email alerts
|

Effective optical response of silicon to sunlight in the finite-difference time-domain method

Abstract: The frequency dependent dielectric permittivity of dispersive materials is commonly modeled as a rational polynomial based on multiple Debye, Drude, or Lorentz terms in the finite-difference time-domain (FDTD) method. We identify a simple effective model in which dielectric polarization depends both on the electric field and its first time derivative. This enables nearly exact FDTD simulation of light propagation and absorption in silicon in the spectral range of 300-1000 nm. where ε ∞ is permitivitty at infin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 18 publications
1
72
0
1
Order By: Relevance
“…The commercial Lumerical FDTD Solutions package is used for the simulations performed in this work. Literature on FDTD simulations of NWs has already shown significant reduction in reflection which is attributed to guided modes, Bloch modes and Fabry-Perot resonances [29][30][31]. Furthermore, it is shown that the geometrical properties of the NW arrays (NWAs) strongly influence the emergence of such modes [13].…”
Section: Simulation Of Reflectance and Power Absorptionmentioning
confidence: 99%
“…The commercial Lumerical FDTD Solutions package is used for the simulations performed in this work. Literature on FDTD simulations of NWs has already shown significant reduction in reflection which is attributed to guided modes, Bloch modes and Fabry-Perot resonances [29][30][31]. Furthermore, it is shown that the geometrical properties of the NW arrays (NWAs) strongly influence the emergence of such modes [13].…”
Section: Simulation Of Reflectance and Power Absorptionmentioning
confidence: 99%
“…For large simulations the method is parallelized via domain decomposition and scales almost linearly with the number of used CPUs [33]. Absorbing materials are simulated by fitting the experimental complex dielectric function by a number of Drude-Lorentz [32] or modified Lorentz [34] terms. There is no restriction on the form of scatterers in FDTD, however a special treatment of fine structures such as thin material interfaces is sometimes required [35].…”
Section: Pc Emissivity Calculation Methodsmentioning
confidence: 99%
“…where, ε∞ is permittivity at infinite frequency, ωp is the pole pair frequency, γp is the damping coefficient , Δεp is the change in relative permittivity due to change in p'th pole and εs is zero frequency relative permittivity [3]. Here, ωp, γp , γ'p are in 1/μm and speed of light is unity.…”
Section: Formulationmentioning
confidence: 99%